KETERAMPILAN MENULIS SURAT YANG BAIK DAN BENAR - Vidya Octa Sari (Universitas Muhammadiyah Kotabumi, 2018)
In the daily life, someone always uses communication tools to connect and talk with others. One of the communication tools used is by writing letters. A letter is a communication tool in written form with the aim that someone can communicate to convey information, messages, questions or in accordance with the wishes of the author. In accordance with this objective, there are several requirements that must be taken into account in making the letter. In fact, there are many more mistakes that we often encounter in terms of tattooing the letter. For the diagnosis of this paper is made with the aim to know the systematic way of writing letters that are good and true. Information or messages that can be conveyed well by the readers.